An Empirical Analysis of Auditor Independence in the Banking Industry - Kanagaretnam, Kiridaran; Krishnan, Gopal V.; Lobo, Gerald J. (The Accounting Review, 2010)
ABSTRACT: We examine auditor independence in the banking industry by analyzing the relation between fees paid to auditors and the extent of earnings management through loan loss provisions (LLP). We also examine whether this relation differs across large banks whose managements are required under the Federal Deposit Insurance Corporation Improvement Act to evaluate internal control over financial reporting and whose auditors must attest to the effectiveness of such internal controls, and small banks that are not subject to those requirements. We find that unexpected auditor fees are unrelated to earnings management for large banks. For small banks, we find greater earnings management via under-provisioning of LLP by banks that pay higher unexpected total and nonaudit fees to the auditor. These results suggest that auditor fee dependence on the audit client is associated with earnings management via abnormal LLP and is a potential threat to auditor independence for small banks. Our findings are relevant to policymakers contemplating new regulations in light of the recent banking crisis.